Pengertian Sosiologi dalam Konteks Pendidikan - Arini Hidayati; Ahmad Ali Wafi; Fadilatul Fauziyah; M. Khoiruddin; Asnawan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Educational sociology is a branch of sociology that examines the relationship between education and society as well as various social processes occurring within educational systems. This study aims to understand education as a social process that contributes to the development of personality, morality, and individual behavior in social life. The discussion covers the definition of educational sociology according to experts, its scope, objectives, and historical development. The scope of educational sociology includes the relationship between educational systems and social systems, social interactions within schools, the relationship between schools and communities, and the influence of education on learners. Furthermore, educational sociology serves as an analytical tool for understanding socialization processes, social development, and the role of education in social change. The historical development of educational sociology is closely associated with the contributions of prominent scholars such as Lester Frank Ward, John Dewey, Emile Durkheim, Karl Mannheim, and George Payne, who significantly influenced the growth of this discipline. Therefore, educational sociology serves as an essential foundation for understanding educational issues through a social perspective to improve the quality of education and community life.